Continuous crystallization of paracetamol exploiting gas–liquid flow in modular nucleation and growth stages. (2nd February 2022) - Fatemi, Naghmeh; Devos, Cedric; Van Gerven, Tom; Kuhn, Simon
Graphical abstract: Highlights: A continuous crystallizer with an in-line nuclei generator has been designed. Gas bubbles are used within a flow crystallizer as heterogeneous nucleation sites. Control of the mean crystal sizes is achieved. Clogging of the crystallizer is prevented. Abstract: A modular multiphase flow crystallizer set-up for the continuous crystallization of paracetamol with an in-line nuclei generator has been developed. Gas bubbles are introduced in a capillary to provide heterogeneous nucleation sites and enhance the nucleation rate. Taking advantage of the separate nucleation and growth sections, control over crystal size distribution is achieved without compromising its span. Comparison with batch growth showed smaller crystal sizes as well as narrower span for the continuous growth. Different configurations of the setup were investigated with regard to the presence of the gas in nucleation and growth sections. Reproducible results were only obtained when gas is present both in the nucleation section (as microbubbles) and in the growth section (as gas slugs). Yields of up to 71% were obtained. Taking the growth time and temperature as varying parameters, the mean crystal size could be manipulated.